Malignant Perivascular Epithelioid Cell Tumor of the Esophagus - Matteo Fassan; Mauro Cassaro; Massimo Vecchiato; Roberto Clemente; Gianmaria Pennelli; Stefano Merigliano; Giuseppe Altavilla (Case Reports in Pathology)
Malignant perivascular epithelioid cell tumor (PEComa) is a rare tumor composed of hybrid tumor cells characterized by immunoreactivity for both melanocytic and smooth muscle markers. This paper describes the uncommon esophageal location of an 8 cm PEComa in a 75-year-old Caucasian man who was presented with ingravescent dysphagia. Although PEComas arising within the gastrointestinal tract are exceptional findings, clinicians should not exclude this class of tumors in the diagnostic investigation of a bulky lesion of the esophageal wall.